Implementasi Kurikulum 2013 Pada Mata Pelajaran Bahasa Arab Untuk Meningkatkan Belajar Siswa - Erlin; Zumrotus Sangadah; Hidayatul Munawaroh (STAI AL-AMIN, 2024)
The purpose of this research is to determine the implementation of the 2013 Curriculum in Arabic Language Subjects to Improve the Learning of Grade 2 and 5 Mi Ma'arif Tegalgot Students. This research is considered important because the delivery of material in Arabic subjects is not easy for all students to understand. The method used in this research is qualitative with a phenomenological type. The informants in this research were the school principal and homeroom teachers for grades 2 and 5, with data collection using interview techniques. The results of the research explain that for learning this school uses the 2013 curriculum, which is applied at both low and high grade levels. The teaching methods used in the lower grades include lectures, discussions, reading and memorization. Evaluations used in the high grades include written and practical tests. , while in lower classes, evaluation is carried out through daily tests or memorizing vocabulary as measured by scores, as well as writing vocabulary. Several suggestions based on information provided in interviews with class 2 and homeroom teachers regarding the implementation of the independent curriculum: Use of the 2013 Curriculum, Obstacles in Lower Grades, Variants of Teaching Approaches, Comprehensive Evaluation, Use of Learning Media.